CHALLENGES AND FUTURE OPPORTUNITIES OF FINANCING URBAN SERVICES - Aydrous, Arif Elhag (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2023)
The development of the urban grounds has turned out to be a vital aspect of the overall growth and betterment of the financial service sector. Through the bridging of the gap between the living standards of the population in the urban periphery, the proposition of an economic equilibrium can be maintained. With the rise in the financial budget for urban services, future opportunities such as the growth of sustainable architecture, the decline in climate change, and the effective utilization of land-based finance can be achieved. However, issues related to the lack of innovative measures to decline the steep prices of sustainable buildings or the weak absorptive capacity of the cities. The study has focused on several shortcomings and the futuristic viewpoint of applying potential financial measures to urban services